Serum bone resorption markers and 25-hydroxyvitamin D level in women of the Trans-Baikal region of the Russian and Buryat nationalities - S. V. Verkhoturova; V. V. Gorbunov; S. Yu. Tsarenok; T. A. Aksenova; N. A. Iljamakova (Сибирский научный медицинский журнал, 2022)
Osteoporosis (OP) is a metabolic bone disease, characterized by a decrease of bone mineral density, leading to the development of low-energy fractures. Serum pyridinoline (PYD) and C-terminal cross-linking telopeptide type I (β-CrossLaps) are among the specific markers of bone resorption. Vitamin D is involved in the metabolism of bone tissue, its deficiency accelerates the processes of bone tissue breakdown. Material and methods. 60 women with osteoporosis were studied (30 Russian and 30 Buryat nationalities) aged 50 to 80 years; the control group included 20 women (10 Russian and 10 Buryat nationalities). Serum bone resorption markers, namely pyridinoline and β-CrossLaps, 25-hydroxyvitamin D (25(OH)D) were measured using immunoassays. Results and discussion. The level of β-CrossLaps was higher and the content of 25(OH)D was lower in women with osteoporosis compared to the control group. There was a positive relationship between β-CrossLaps concentration and body mass index < 20 kg/cm2 , frequent falls, and a hip fracture, between the level of 25(OH)D and hereditary history of osteoporosis in Russian women. There was a positive relationship between Serum pyridinoline and smoking, between 25(OH)D and low physical activity, β-CrossLaps and the major osteoporotic fractures in Buryat women. It was found that the β-CrossLaps is an independent predictor of the development of fractures in Russian women (β = 0.678, p = 0.04). In Buryat women, independent predictors of fractures are pyridinoline (β = –0.38, p = 0.04) and β-CrossLaps (β = 0.671, p = 0.01). Conclusions. The systemic markers of bone resorption (pyridinoline, β-CrossLaps) and 25(OH)D can be used in the diagnosis of osteoporosis and fractures in residents of the Trans-Baikal Region in addition to risk factor assessment and bone mineral density measurement.